Orientasi Kewirausahaan dan Karakteristik Perusahaan terhadap Perkembangan Usaha (Studi pada Industri Kecil Bidang Agro dan Hasil Hutan di Kabupaten Garut) - Husni Muharam (Jurnal Wacana Ekonomi, 2019)
This research is motivated by a view that business development is an important factor for a company in order to survive in the fierce business competition. Business development can be obtained if the company can improve entrepreneurial orientation and understand the characteristics of the company. The purpose of this study was to analyze the effect of entrepreneurial orientation and company characteristics on business development in the Small and Medium Agro Industries that have Industrial Registry Numbers in Garut Regency. This research is a descriptive and verification research. Descriptive research is used to describe respondents' perceptions of entrepreneurial orientation variables, company characteristics and business development. Verification research is used to determine the effect of entrepreneurial orientation variables and company characteristics on business development. This survey involved 81 Agro-Sector IKMs that had Industrial Registry Numbers. The sampling technique used simple random sampling. Data collection was carried out through interviews, questionnaires and surveys. The data analysis used was the Partial Least Square (PLS) statistical approach. The results show that of the three research variables descriptively all of the criteria are quite high. The influence of entrepreneurial orientation and company characteristics on business development shows a significant positive effect.